2021
DOI: 10.3389/fgene.2021.707228
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Core Melanin Synthesis Genes Provides Novel Insights Into the Molecular Basis of Albinism in Fish

Abstract: Melanin is the most prevalent pigment in animals. Its synthesis involves a series of functional genes. Particularly, teleosts have more copies of these genes related to the melanin synthesis than tetrapods. Despite the increasing number of available vertebrate genomes, a few systematically genomic studies were reported to identify and compare these core genes for the melanin synthesis. Here, we performed a comparative genomic analysis on several core genes, including tyrosinase genes (tyr, tyrp1, and tyrp2), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…We subsequently detected the expression level of microphthalmia-associated transcription factor (MITF), which is the master transcription factor that regulates melanogenesis by activating the transcription of downstream melanogenic genes including tyr, tyrp1, dct and pmel [53,56]. Although the two coding gene copies of mitf (mitfa and mitfb) did not show significant expression difference between the two skin types at the transcriptional level (figure 5c), we demonstrated that the nuclear phospho-MITF(Ser180) protein level in YM group was significantly higher than that in WT group by western blotting (figure 5d), which should be the reason for the upregulated expression of the above-mentioned melanogenic genes [57][58][59][60].…”
Section: The Expressions Of Core Melanogenesis Genes and Nuclear Phos...mentioning
confidence: 99%
“…We subsequently detected the expression level of microphthalmia-associated transcription factor (MITF), which is the master transcription factor that regulates melanogenesis by activating the transcription of downstream melanogenic genes including tyr, tyrp1, dct and pmel [53,56]. Although the two coding gene copies of mitf (mitfa and mitfb) did not show significant expression difference between the two skin types at the transcriptional level (figure 5c), we demonstrated that the nuclear phospho-MITF(Ser180) protein level in YM group was significantly higher than that in WT group by western blotting (figure 5d), which should be the reason for the upregulated expression of the above-mentioned melanogenic genes [57][58][59][60].…”
Section: The Expressions Of Core Melanogenesis Genes and Nuclear Phos...mentioning
confidence: 99%
“…The top 10 enriched GO-terms in the upregulated gene set mostly involve pigmentation (pigment metabolic process, pigment biosynthetic process, melanosome organization, pigment granule organization, melanocyte differentiation, pigmentation, developmental pigmentation). One of the central DEG driving this enrichment is the mitfa transcription factor, which is known to signal downstream of BMP and governs melanocyte differentiation and development via tyrosinase (log FC tyr 2.01), tyrosinase related protein 1 (log FC tyrp1a 1.82 and log FC tyrp1b 2.08), the premelanosome protein (log FC pmela 1.44 and log FC pmelb 3.66), dopachrome tautomerase (log FC dct 2.6), and the melanosomal transporter (log FC slc24a5 2.35) 49,50 . The top 10 enriched GO-terms in the downregulated gene set are linked to negative regulation of proteolysis (negative regulation peptidase activity, negative regulation proteolysis, regulation of peptidase activity, negative regulation of endopeptidase activity, regulation of proteolysis) and immune response (regulation of immune response, positive regulation of immune system process) ( Supplementary Table 5-6 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, genes classified in the melanin pathway could be affecting production of dopamine or melatonin. Involvement of genes within the melanin pathway as players in cave-specific traits, both pigmentation and other traits, has been documented in multiple cases [ 23 - 28 ].…”
Section: Discussionmentioning
confidence: 99%